The Effectiveness of Group Counseling Services with Reality Approach in Improving Broken-Home Students' Resilience - Welmi Yulisa; Masril Masril; David David (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study aims to see whether or not the reality approach group counseling service is effective in improving the self-resilience of broken home students at SMK Kosgoro 2 Payakumbuh. This study used a true experimental design, namely the pretest-posttets control group design in which the population was 60 people and the research sample was 22 people. The data collection tool used was a questionnaire. The data analysis technique used is non-parametric statistics with the Wilcoxon Signed Rank test. The results of the study were related to the reality approach group counseling in improving the self- resilience of broken home students, so the statistical test results from the Wilcoxon Signed Ranks test showed that W_count ÔëÑ Wtable (66 ÔëÑ11) with Z = -2.93 and from the statistical results theasymptotic sig value (2-tailed) 0.003. Because for the 2-way test of 0.05, sig 0.003 Ôëñ 0.05 with Z = -2.93. These data indicate that the reality approach group counseling approach is effective in improving the self-resilience of broken home student.